Три новых вида комаров-лимониид (Diptera, Limoniidae) фауны СССР - Савченко, Е.И. (Вестник зоологии, 1983)
Dicranota (Rhaphidolabis) ferruginea Sav., sp. n. (Kirghiz SSR, Issyk- Kul lake shore), Phyllolabis ghilarovi Sav. sp. n. (Armenian SSR, Lichk), Ormosia (s. str.) longispina Sav. sp. n. (Armenian SSR, Megradzor) are described. From allied species they differ in all features of the male hypopygium structure. Type material of des- cribed species is preserved in the collection of the Institute of Zoology, Ukrainian Academy of Sciences (Kiev).